Resilience in the Population of Cusco in Times of COVID-19 - Guevara , Ronny Andree Chacon; Ticona , William Edward Pino; Mamani , Emilio Flores; Obregon , Flavio Salas; Quiroz , Nicanor Rolando Martinez; Rojas , Erika Paola Serrano (Journal of Ecohumanism, 2024)
The COVID-19 pandemic has profoundly impacted the world, leading to millions of infections, deaths, and crises. In Cusco, Peru, this complexity has altered social structures and interpersonal relationships. This study aimed to explore human adaptation strategies developed during the pandemic in Cusco. A non-probabilistic sample of 40 adults from the province’s eight districts was interviewed using phenomenological and ethnomethodological methods. Data were collected through in-depth interviews and analyzed using Atlas Ti software. Results indicate that the pandemic has changed personal and social characteristics, reflected in altered moods, worries, and priorities. Participants reported increased awareness of their vulnerability, heightened solidarity with others, and shifting family roles that necessitated new forms of coexistence, often with distorted responsibilities. Interpersonal communication became limited, relying heavily on technology, and there was a rise in individual responses, including the use of natural and chemical remedies. Overall, the study concludes that Cusco’s inhabitants have developed various adaptation strategies to confront the pandemic, significantly impacting their personal lives and social contexts.